2007
DOI: 10.1007/s00018-007-7375-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of transcriptional factors Sp1, c-Rel, and c-Jun in LPS-induced C/EBPδ gene expression of mouse macrophages

Abstract: Transcription factor C/EBPs are involved in the regulation of various cellular responses. Here, it was suggested that C/EBPdelta gene was activated by lipopolysaccharide (LPS) through transcription factors Sp1, c-Rel, and c-Jun. Assay of the luciferase reporter vectors containing a 5'-deletion of the C/EBPdelta gene promoter indicated that a LPS-responsive element was positioned between -345 and -35 bp of mouse C/EBPdelta gene promoter. Transcription factors Sp1, c-Rel, and c-Jun bound to this region were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…Previous studies mention C/EBPd regulation and conclude that NF-kB, Erk1/2, and c-Jun recruitment by Sp1 are important [Liu et al, 2007]. In this study, we found that there is no obvious alteration in the activation of NF-kB and Erk1/2 in LPS-treated cells after TSA treatment (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 35%
See 3 more Smart Citations
“…Previous studies mention C/EBPd regulation and conclude that NF-kB, Erk1/2, and c-Jun recruitment by Sp1 are important [Liu et al, 2007]. In this study, we found that there is no obvious alteration in the activation of NF-kB and Erk1/2 in LPS-treated cells after TSA treatment (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 35%
“…Moreover, COX-2 accumulation has been detected in different tumor types [Dempke et al, 2001;Gately and Kerbel, 2003;Toomey et al, 2009]. Previous studies have indicated that LPS can induce COX-2 expression via activation of NF-kB and upregulation of C/EBPs [Woo et al, 2006;Liu et al, 2007]. Herein, we also found that COX-2 could be induced, and in parallel, NF-kB Fig.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…15,16 A previous report indicated that expression of some C/EBP family member may be regulated by MAPKs and NF-B. 17 To examine possible involvement of MAPKs or NF-B in the induction of C/EBP␤ by ER stress, we pretreated mesangial cells with selective inhibitors of extracellular signal-regulated kinase (PD098059), JNK (SP600125), p38 MAPK (SB203580), or NF-B (SC-514); stimulated them by thapsigargin; and subjected them to Northern blot analysis. Our preliminary results showed that SP600125 but not other inhibitors attenuated induction of C/EBP␤ by ER stress (Supplemental Figure S3), indicating possible involvement of JNK.…”
Section: Discussionmentioning
confidence: 98%